Contralateral ovarian endometrioma recurrence after unilateral salpingo-oophorectomy - Tokie Hidari; Tetsuya Hirata; Tomoko Arakawa; Kaori Koga; Kazuaki Neriishi; Shinya Fukuda; Akari Nakazawa; Natsuki Nagashima; Suke Ma; Hui Sun; Masashi Takamura; Miyuki Harada; et al. (BMC, 2019)
Abstract Background The recurrence rate after unilateral salpingo-oophorectomy (USO) for unilateral endometrioma has not been reported. We evaluated the rate of and risk factors for endometrioma recurrence after USO. Methods In this retrospective observational study, we enrolled 110 women (age, 35-45 years) who underwent laparoscopic USO (n = 50) or cystectomy (n = 60) for unilateral ovarian endometrioma from January 2010 through December 2012. We compared patients' characteristics between patients who underwent USO and those who underwent cystectomy. We also compared patients with and without an endometrioma recurrence after USO using univariate and multivariate stepwise logistic regression models to identify recurrence risk factors. Endometrioma recurrence was defined as an ovarian cyst (> 2 cm) with features typical of an endometrioma identified by postoperative transvaginal sonography. Results Endometrioma recurred in 8 (16%) patients after USO (mean follow-up, 46.0 ± 12.9 months [range, 15-73]). The post-USO cumulative recurrence rates at 12, 24, 36, and 60 months were 8.0, 10.2, 12.7, and 24.7%, respectively (Kaplan-Meier analysis). In logistic regression analysis, a contralateral side adhesion score ≥ 4 was an independent risk factor for endometrioma recurrence after USO (odds ratio, 19.48, 95% confidence interval, 1.59-237.72). The post-USO cumulative recurrence rates at 12, 24, 36, and 57 months were 19.5, 24.1, 31.0, and 54.0%, respectively, in cases with contralateral side adhesion scores ≥4, and 0.0, 0.0, 0.0, and 5.9%, respectively, in cases with scores < 4 (log-rank test, P = 0.0023). Conclusions To our knowledge, this is the first report on the recurrence rate and risk factors associated with recurrence after USO. Endometrioma recurrence rates were 24.7% during the first 5 years after USO. The post-USO recurrence rate increased significantly in cases with contralateral side adhesions. Our findings could improve the planning of USO and patient selection for postoperative hormonal therapy.